On Matrix‐Clause Intervention in Accusative‐and‐Infinitive Constructions. (27th May 2019) - Neeleman, Ad; Payne, Amanda
Abstract: One of the strongest arguments for a raising‐to‐object analysis of English accusative‐and‐infinitive constructions comes from the fact that adverbials and particles belonging to the matrix clause can intervene between the embedded subject and the embedded predicate. We reevaluate this argument in the light of a neglected alternative analysis, namely that matrix‐clause intervention is the result of extraposition of the embedded predicate. We show that this analysis gives a better account of matrix‐clause intervention than raising to object. Our arguments are based on the scopal properties of the embedded subject and on the order among multiple intervening elements. We also consider various mixed analyses that feature both raising to object and extraposition. These turn out to be conceptually awkward and empirically flawed.